Experimental study of pedestrian flows including crutch users through a bottleneck with different angles. (28th October 2021) - Hu, Yanghui; Pan, Hongliang; Zhang, Jun; Song, Weiguo
Abstract: There is a great demand for the transportation safety of pedestrian crowd including crutch users considering the rapidly aging and physically disabled population as well as the increased potential safety hazard in areas with a dense population. To investigate the pedestrian dynamics of lower-body disabled or injured people, we performed pedestrian experiments in bottlenecks by considering different angles of the bottleneck in heterogeneous crowd with different numbers of crutch users. It is shown that the average velocities of crutch users are 7.1%–22.2% smaller than those of able-bodied participants. With the increase of crutch numbers, the proxemic values of crutch users decrease as a linear function. Compared with the other three angles (0°, 15°, 30°), the flow rate in the 45° bottleneck is higher with less waiting and congestion. However, crutch users receive a larger repulsion effect at angle 45° considering their larger proxemic values. The results in this study are valuable for the facility design and evacuation guidance in the pedestrian flow including crutch users through bottlenecks.